Het Dier in de Kunst. - Juwet, Willy; Hof ter Nederloo, Sint-Pieters-Leeuw; BBL (Bank Brussel Lambert) Brussel (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1988)
Besard, Hugo ; Boffin, Fred ; Bolle, Jos ; Calmeyn, Jan ; de Groote - Tanghe, Georgette ; Derore, Joël ; Devreux, Pierre ; Grooters, Patrick ; Landuyt, Octave ; Mara, Pol ; Meysmans, Willy ; Moerman, Piet ; Poot, Rik ; Stenmans, Eric ; Szymkowicz, Charles ; Van Ruysevelt, Luc
Het Dier in de Kunst, Hof ter Nederloo, Sint-Pieters-Leeuw, 11 maart - 24 april 1988
boek